Tri Hita Karana Implementation in Accommodation Management (The Case of Traditional Balinese Homestays in Ubud) - Solihin; Ida Ayu Ketut Sumawidari (Catuspata Press, 2021)
Abstract : Purpose: This research paper discusses the implementation of Tri Hita Karana in the development and management of traditional Balinese homestays in Ubud, Bali, Indonesia. Research methods: The qualitative research which data are obtained through observation, literature study, and in-depth interviews with several informants, namely observers of Balinese cultural tourism and owners and managers of homestays in Ubud. Findings: Traditional Balinese homestays in Ubud are buildings where local residents live in the form of umah